Hydrochloric Acid Infusion for the Treatment of Metabolic Alkalosis in Surgical Intensive Care Unit Patients. Issue 6 (June 2018) - Guffey, Jason D.; Haas, Curtis E.; Crowley, Amber; Connor, Kathryn A.; Kaufman, David C.
Background: Older reports of use of hydrochloric acid (HCl) infusions for treatment of metabolic alkalosis document variable dosing strategies and risk.Objectives: This study sought to characterize use of HCl infusions in surgical intensive care unit patients for the treatment of metabolic alkalosis.Methods: This retrospective review included patients who received a HCl infusion for >8 hours. The primary end point was to evaluate the utility of common acid-base equations for predicting HCl dose requirements. Secondary end points evaluated adverse effects, efficacy, duration of therapy, and total HCl dose needed to correct metabolic alkalosis. Data on demographics, potential causes of metabolic alkalosis, fluid volume, and duration of diuretics as well as laboratory data were collected.Results: A total of 30 patients were included, and the average HCl infusion rate was 10.5 ± 3.7 mEq/h for an average of 29 ± 14.6 hours. Metabolic alkalosis was primarily diuretic-induced (n = 26). Efficacy was characterized by reduction in the median total serum CO2 from 34 to 27 mM/L ( P < 0.001). The change in chloride ion deficit and change in apparent strong ion difference (SIDa) were not correlated with total HCl administered. There were no documented serious adverse effects related to HCl infusions.Conclusion: HCl was effective for treating metabolic alkalosis, and no serious adverse events were seen. In this clinical setting, the baseline chloride ion deficit and SIDa were not useful for prediction of total HCl dose requirement, and serial monitoring of response is recommended.